До 90-ї річниці часопису "Краєзнавство" (1927–2017): історія, статистика, особливості - Бажан, О.; Левченко, В.; Левченко, Г. (Краєзнавство, 2017)
У статті проаналізовано структуру і рубрики, редакційний та авторський склади, основні напрями
проблематики публікацій та пріоритетні тенденції розвитку часопису «Краєзнавство». The article analyses the structure and headings drafting and architectural compositions, the main directions
of perspective publications and priority development trends of the journal «Krayeznavstvo». Until the journal
receives articles from many educational institutions and research institutions of Ukraine. In the selection of
articles for publication in the journal, the editorial Board tries to hold the balance between articles from experts
from different regions of the country, the intelligence of young scientists (students and post-graduates) and
works of famous scientists. Demonstrated that the magazine occupies a worthy place in the vast array of diverse
species and typological features of Ukrainian historical scientific serial publications as an important element
of scientific communication and effective means of integration for researchers in the field of local history to
world scientific space. Thanks to an interesting and topical subject and an authoritative editorial Board and a
high level of publications, printing performance, skilled work of the editors and the entire editorial team of the
journal is recognized by authors and readers as one of the leading scientific serials periodicals.With the revival
of the journal «Krayeznavstvo» 1993, he became a tribune for discussion and publication of factual and theoretical
research local history direction. A distinctive feature of the magazine was a print function on the network
of local history institutions in the country, horn of local history to the public. В статье проанализирована структура и рубрики, редакционный и авторский составы основные направления проблематики публикаций и приоритетные тенденции развития журнала «Краеведение».